The implementation of educational games to enhance elementary school students' interest in mathematics - Yosafat Manindo Turnip; Robert Soesanto (Universitas Sarjanawiyata Tamansiswa, 2023)
The present study is motivated by the issue of low interest in mathematics among students in private elementary schools in Jakarta. Despite the abundant resources and infrastructure that support learning, technology has not been fully utilized to enhance students' engagement with mathematics. Consequently, students' learning interest has been declining, which in turn negatively impacts their enthusiasm and passion for learning. The aim of this study is to investigate how the application of educational games can increase the learning interest of elementary school students in mathematics, using a descriptive qualitative method. Educational games offer a convenient and effective means for teachers to deliver material, as they create an active, enthusiastic, and enjoyable learning environment in the classroom. The combination of technology and the role of the teacher is essential in supporting students' learning and developing human resources. By integrating educational games into the curriculum, students' interest and attraction in learning mathematics can be enhanced, making educational games an effective tool for increasing students' learning interest. Based on the findings of this study, the researcher suggests the importance of developing educational games and digital teaching materials, as well as moving away from conventional teaching methods. These recommendations are essential for enhancing students' learning interest and promoting effective learning in the classroom.